Letter From Finland: Inspecting the Finnish governance system for the Sustainable Development Goals - Lessons for Iceland - Jóhann Páll Ástvaldsson 1991- (2021)
The 193 United Nations member states agreed upon the Sustainable Development Goals in 2015, which involve 17 goals to be reached by 2030. The goals are wide-ranging in scope and forced governments worldwide to the drawing board as to how to implement the 169 total targets of the Sustainable Development Goals. Finnish authorities have a long-standing tradition of governing through sustainable development, enjoying a head-start to many of its peers. The Finnish governance system surrounding sustainable development is exemplary in many ways as they have implemented a culture based on a high-level political commitment with intergenerational thinking. This thesis aims to inspect what governance mechanisms the Finnish authorities have in place, and to draw upon those lessons to employ for use for the implementation of the Sustainable Development Goals in Iceland. The research is a qualitative case study focused on the most similar case, comparing Finnish and Icelandic governance surrounding the Sustainable Development Goals. The research builds upon governance theories as well as touching on small state theories and theories of Nordic co-operation. The main findings are that Icelandic authorities can employ a number of mechanisms to improve their implementation of the Sustainable Development Goals. To name a few, increased parliamentary and high-level political commitment would lead to progress in the sphere of sustainable development. Additionally, fostering a culture of inter-generational thinking over short-term values, as well as implementing the Commitment 2050 tool would prove beneficial. However, Iceland should look to keep one of its key governance characteristic, smallness and flexibility.